Sectoral Growth and Income Inequality in ASEAN-5 Countries: Case of Low-Middle Income Economies - Raeskyesa, Dewa Gede Sidan (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2020)
This paper aims to explore the relationship between growth in economic sectors, especially manufacturing, service, and agriculture, towards income inequality. Furthermore, it utilizes panel data for low-middle income ASEAN countries. The result shows that the share of agricultural sector in GDP has a significant and negative relationship with income inequality. In fact, the effect is robust for the incorporation of control variables. Therefore, it underlines the importance of agricultural sector development for reducing inequality and also for fostering ASEAN economic integration.